RETRACTION: DAE‐GAN: An Autoencoder Based Adversarial Network for Gaussian Denoising (Expert systems, 2025)
RETRACTION: A. Samanta, A. Saha, S. C. Satapathy, H. Lin, “DAE‐GAN: An Autoencoder Based Adversarial Network for Gaussian Denoising,” Expert Systems (Early View): e12709, https://doi.org/10.1111/exsy.12709. The above article, published online on 06 May 2021 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the journal Editor‐in‐Chief, David Camacho; and John Wiley & Sons Ltd. The article was submitted as part of a guest‐edited special issue. The retraction has been agreed on as the article was not reviewed in line with the journal's peer review standards. Furthermore, the methodology and model in this manuscript are insufficiently described. Accordingly, the results are not considered reliable. The authors disagree with the retraction.